2010
DOI: 10.3109/1354750x.2010.495787
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of deoxynivalenol intake and urinary deoxynivalenol in UK adults

Abstract: The relationship between deoxynivalenol (DON) intake and first morning urinary DON was examined in UK adults to validate the latter as a biomarker of human exposure. DON was assessed in first morning samples collected during a period of normal diet, a wheat-restriction intervention diet, and partial wheat-restriction intervention in which bread was allowed. During the partial intervention duplicate bread portions were collected for DON analysis. During the normal diet, partial intervention and full interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
107
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 35 publications
5
107
0
1
Order By: Relevance
“…V = daily urine production of adults is 1500 mL and children is 1000 mL (Turner et al, 2010b). BW = body weight (kg) reported in questionnaire.…”
Section: Estimated Dietary Exposure Through Urinary Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…V = daily urine production of adults is 1500 mL and children is 1000 mL (Turner et al, 2010b). BW = body weight (kg) reported in questionnaire.…”
Section: Estimated Dietary Exposure Through Urinary Levelsmentioning
confidence: 99%
“…Reported by Ezekiel et al (2014) Assumptions made: ER = urinary excretion ratio of DON is 72% (Turner et al, 2010b) = urinary excretion ratio of OTA is 50% (Schlatter et al, 1996). V = daily urine production of adults is 1500 mL and children is 1000 mL (Turner et al, 2010b).…”
Section: Estimated Dietary Exposure Through Urinary Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds monitored in this study were deoxynivalenol (DON), deoxynivalenol-3-glucuronide (DON-3-GlcA), T-2-toxin (T-2), HT-2-toxin (HT-2), HT-2-toxin-4-glucuronide (HT-2-4-GlcA), fumonisin B 1 (FB 1 ), aflatoxins (AFB 1 , AFB 2 , AFG 1, AFG 2 , AFM 1 ), zearalenone (ZEA), zearalanone (ZAN), their urinary metabolites α-zearalanol (α-ZEL), and β-zearalanol (β-ZEL) and corresponding 14-O-glucuronic acid conjugates (ZEA-14-GlcA, ZAN-14-GlcA, α/β-ZEL-14-GlcA), ochratoxin A (OTA), and ochratoxin alpha (OT α ), as well as enniatin B (EnB) and dihydrocitrinone (DH-CIT), a urinary metabolite of citrinin (Dunn et al 1983;Ali et al 2015b). Since in previous human or animal studies a good correlation has been observed between dietary mycotoxin intake and urinary excretion, AFM 1 , OTA, DON, FB 1 , and ZEA can be considered as suitable biomarkers of exposure (Zhu et al 1987;Gilbert et al 2001;Šarkanj et al 2013;Turner et al 2010;Riley et al 2012;Gambacorta et al 2013;Muñoz et al 2014). When reliable urinary excretion rates were available, these data were used in our study to calculate the PDI to estimate the human exposure to mycotoxins.…”
Section: Introductionmentioning
confidence: 97%
“…In a study carried out in the United Kingdom by Turner et al [1] a strong correlation was found between these urinary metabolites (the sum of the free DON and DON-3Glu) and cereal intake of the study population. Still in a related study performed by the same group of authors, the mean transfer of DON to urine was estimated to be 72% [2]. For these reasons, detecting and or quantifying the sum of these metabolites (DON and DON-3-glucuronide) in human urine has been recommended for biomonitoring of this toxin…”
Section: Introductionmentioning
confidence: 99%